Re-Analyzing of Consequences and Methods of Climatological Changes Managements (Case Study: Iran’s Central Basin) - Sadegh Karami (تحقیقات کاربردی علوم جغرافیایی)
Importance of climate change is global. This issue to some extent has been out of human control. Human beings can only provide security and the community with knowledge and management against its negative consequences. On the basis of this research, the present paper analyzes the impact of climate change on Iran, on a small scale and applied to the central catchment area. The findings of the research indicate that climate change has shown the geographic region of Iran in terms of changing the rainfall pattern, decreasing precipitation and increasing its temperature. In the next step, these cases resulted in excessive withdrawal of groundwater aquifers and it has reduced the quality of underground water. This chain has led to the design of inter-basin water transmission projects, which is at least the result of the cycle of social tensions that has occurred in recent years. Considering the geographical extent of the basin and its belonging to one of the most frequent aspects of Iran's civilization, the set of consequences of climate change in the central catchment area, in addition to its impact on various social, political, economic and environmental layers, also has several scale effects. And its destructive effects go beyond national scale and to an extent beyond the scope of Iranian culture. In this regard, the research findings indicate that climate change in the central watershed is influential in many aspects of society and the country, so that if the current process continues, the current Iranian civilization will face a strategic challenge. To this end, at the end of the research, good water governance, as the best way to confront and control the negative consequences of climate change on the central catchment area, and Iran in general, has been argued.